AL-SHAYKH MAIMOEN ZUBAIR WA AFKĀRUH ‘AN AL-ISLĀM WA AL-WAṬANIYAH WA AL-TASĀMUH FĪ INDŪNĪSIYĀ (State Islamic University (UIN) of Sunan Ampel Surabaya, 2021)
The article examines the thoughts of Maimoen Zubair (1929–2019), one of Indonesia's most eminent traditional Muslim scholars, in relation to his attitudes and views on issues of nationality and religious tolerance. Examining this subject is critical because the community's tolerance level is declining, and few studies examine the figures' perspectives on the subject. To gain a better understanding of Maimoen Zubair's thoughts, this research employed a qualitative approach, which included an interview with him and an analysis of his works and lectures. The study finds that Maimoen Zubair holds progressive views on nationality issues, emphasizing the critical importance of preserving nationalism as a means of uniting a nation. This is something that all communities, regardless of their religious affiliation, should do. Individuals cannot worship in peace and comfort if communal conflicts occur. According to him, a country will achieve unity when its citizens respect and tolerate one another. His attitudes and views are derived from traditional Islamic teachings and the traditions of Pesantren (Islamic boarding school), where he studied. Maimoen Zubai's views on nationality are widely accepted in Indonesia, not just among Muslims.